Influencers' Own Brands : Investigating the Drivers of Young Female Followers' Purchase Intentions towards Influencers' Own Brands - Bergström, Vilma; Fredriksson Johansson, Jennifer (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2023)
Influencers have been working with collaborations with different brands during a long period of time, the latest development in their career has been to launch their own brands without any intermediators. Previous studies have investigated influencers' own brands but there is still a knowledge gap between intention and behavior. To fill the gap about this subject it is relevant to further expand on the underlying drivers by expanding the variables to get a deeper understanding for the purchase intentions that drives purchase behavior. Therefore, the purpose of this report is to get a deeper understanding of the drivers underlying young female followers' purchase intentions towards influencers' own brands in the category of beauty products. To answer this research purpose, the “Theory of Reasoned Action” has been used and through that a theoretical framework has been developed. The data was collected through semi-structured interviews with young females (18 to 30 years old) living in Northern Sweden. The interview questions focused on the females shopping habits, attitudes, subjective norm, previous experiences and purchase intentions towards influencers' own brands. In order to analyze the data a thematic analysis was used. The interview respondents were divided into two groups depending on whether they have purchased a product from an influencer's own brand or not to be able to find out if there were any differences or similarities between them. The result showed that attitudes of influencers in general and subjective norms did not have a big impact on the participants' purchase intention towards influencers' own brands. However, attitudes towards influencers' own brands had an impact on purchase intention. More important factors were also their shopping habits and previous experience from influencer marketing.